(3cJGH OSJhQ GdWH aj SQ GdUfGYI hHQD SGYIs - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRi cfJ YfO GdhRjQ GdbGSe Hf YHO Gddg aLQi HMVQJg PcQ TF ef GdWH s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B:(3` ChjTe TF ef GdCajhf GdLjO GdeUQi hjLYd efg ai GUOGZI Ch jCNP TjFkG ef GdYfGHI Ch TQGHI Ch jCcd eQbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs